Contexto capacitante para inovação em programas de aceleração em Curitiba: mapeamento do processo de construção do conhecimento em aceleradoras de startups, à luz da teoria ator-rede e do conceito de ba - Gomes, Rhodrigo Deda (2018)
The aim of this study is to map the environment of six accelerators in Curitiba and the dynamics of human and nonhuman actors' relations in the construction of knowledge of startups, between 2015 to 2017, considering them as spaces of knowledge creation. In order to do so, the human and non-human actors are identified, the relationships between them in the networks of the six environments and the knowledge creation characteristics generated in these environments. It is proposed to map the process of knowledge construction in startups training programs. The research has a descriptive and explanatory character, because it identifies the relations between human and non human actors in training programs and the characteristics of knowledge creation, in order to present a broader view of this whole process. Concernig the methodological design, the study is eminently a field research, using semi-structured interviews and questionnaires, without neglecting the bibliographic character as well. The research allows to describe the networks of human and nonhuman actors in training programs in Curitiba, as well as to understand the characteristics of the knowledge environment and the knowledge network of entrepreneurs of startups who participate in the programs. The result of this study enables accelerators to know different models of training programs and identify opportunities for improvement in their innovative knowledge environments.